1984
DOI: 10.1111/j.1365-2028.1984.tb00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Food of the golden jackal (Canis aureus) in central Niger

Abstract: Summary Predation on domestic livestock in central Niger, especially by the golden jackal (Canis aureus (L.)), has been identified by herders as a problem second only to small stock disease. A standard questionnaire was used to gather information on herders' losses to predation. To determine food habits of jackals in the region, 143 scat samples were collected. Laboratory analysis of the scats showed that vegetable matter and invertebrates constituted the main identifiable items in the diet. Unidentified mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
1
16
0
1
Order By: Relevance
“…This was consistent with observations made elsewhere (Schaller, 1967;Johnsingh, 1983;Stuart, 1983;McShane & Grettenberger, 1984;Palmer & Fairall, 1988;Mukherjee, 1989;Sultana & Jaeger, 1989;Weisbein & Mendelssohn, 1990;Avenant & Nel, 2002). Studies on jungle cats and golden jackal have shown rodents to occur in more than 60% of the scats analysed (Schaller, 1967(Schaller, , 1970Johnsingh, 1983;McShane & Grettenberger, 1984;Sultana & Jaeger, 1989). However, comparisons based on just percentage frequencies can be misleading.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with observations made elsewhere (Schaller, 1967;Johnsingh, 1983;Stuart, 1983;McShane & Grettenberger, 1984;Palmer & Fairall, 1988;Mukherjee, 1989;Sultana & Jaeger, 1989;Weisbein & Mendelssohn, 1990;Avenant & Nel, 2002). Studies on jungle cats and golden jackal have shown rodents to occur in more than 60% of the scats analysed (Schaller, 1967(Schaller, , 1970Johnsingh, 1983;McShane & Grettenberger, 1984;Sultana & Jaeger, 1989). However, comparisons based on just percentage frequencies can be misleading.…”
Section: Discussionsupporting
confidence: 90%
“…The resource dispersion hypothesis of Macdonald (1983) suggests that carnivore territory size is influenced by the dispersion of food. We have no quantitative information on jackal diet, or on the abundance and distribution of wild prey, but studies elsewhere indicate that jackals are omnivorous opportunists with varied diets ranging from fruit to invertebrates, small mammals, antelope and livestock (Schaller, 1967; Kruuk, 1972; Lamprecht, 1978; Moehlman, 1983; McShane & Grettenberger, 1984). We suspect, however, that the conversion of natural habitats to farmland in Bale may have reduced the availability of wild prey, particularly rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to coexist is not surprising considering the variability of habitat use, activity patterns, and feeding ecology exhibited by each species throughout its wide distribution (e.g. Rosevear, 1974;Taryannikov, 1974;Macdonald, 1979;Ferguson et al, 1983;Smithers, 1983;McShane & Grettenberger, 1984;Avery et al, 1987;Hiscocks & Perrin, 1987;Poche et al, 1987).…”
Section: Discussionmentioning
confidence: 99%